Relationship between adolescent smartphone use and peer attachment and nomophobia - Molu, Birsel; Özpulat, Funda; Baş, Melike Taşdelen (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Nomophobia is fear of being without a cell phone or being unable to use one. This paper investigated the effect of friendship attachment on nomophobia in adolescents. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This descriptive cross-sectional study was conducted in five high schools in the Central Anatolia Region of Türkiye. The sample consisted of 1033 adolescents. Data were collected using a personal information form, the Adolescent Friendship Attachment Scale, and the Nomophobia Questionnaire. Data analysis was conducted using parametric tests such as One-Way ANOVA and Independent Sample t-Test, with Bonferroni tests for post-hoc comparisons. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The majority of participants were girls (58.3%), lived in nuclear families (76.2%). Most students used their smartphones for 2-4 hours daily (40.3%), and were active on social media (86%). The study found significant differences in phone usage time and friend attachment scores among different age groups. Women had higher friend attachment scores and nomophobia scores compared to men. Social media use was associated with higher nomophobia and friend attachment scores. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Adolescents’ smartphone uses characteristics influence their nomophobia levels and friendship attachment styles. Professionals should plan interventions to raise adolescents’ awareness of nomophobia.